Family and social class differences in sports behavior motivation among college students: An empirical study based on the latent class model - Liu, Liping; Chen, Shanping; Yang, Xueyan; Yang, Yuqing (Frontiers in Psychology, 2023)
Objective: This paper explores the classification of latent characteristics of college students' sports behavior motivation, analyzes the relationship between the latent class of college students' sports behavior motivation and family social class, and provides a theoretical basis for teaching students in accordance with their aptitude in the integration of sports and education. Participants: In total, 1,092 college students were investigated in this study. Methods: The "University Student Sports Behavior Motivation Survey Questionnaire" was used to investigate college students, and the latent profile analysis was used to classify the types of college students' sports behavior motivation and the characteristics of sports behavior motivation of college students from different families, and social classes were further analyzed. Results: College students' sports behavior motivation types can be divided into 4 categories: "low motivation type" accounted for 0.82%, "healthy appearance type" accounted for 11.45%, "healthy fun type" accounted for 37.36%, and "high motivation type" accounted for 50.37% The higher the social class of the family, the more sports behavior motivation of college students tends to be healthy appearance, health and fun, and high motivation; the lower the family social class, the more motivational sports behavior of college students tend to be low motivation; the better the perception of personal health The higher the probability that college students belong to the high-motivated type, the fewer the college students with chronic diseases are more likely to belong to the healthy appearance and high-motivated type. Conclusion: There is a certain relationship between the types of college students' sports behavior motivation and family social class. Therefore, in implementing the sports and education integration policy, physical education should be based on the needs of college students' sports behavior motivation. Undergraduates from lower social strata carry out precise interventions on their sports behavior motivation, increase participation, and comprehensively promote the health of college students.